(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
White papilloma are rare lesions that may occur at any site of mucosa- lined respiratory tract especially in vocal cords. Morphologically it appears villas looking, clinically & microscopically benign in most cases. We report a 70 years old male patient with white papilloma near anterior commissure involving both vocal cords found during indirect laryngoscopy. The lesion was completely resected with a unipolar coagulation device under direct laryngoscopy. Histopathological examination showed papilloma of vocal cords associated with Human papilloma virus(HPV) wart. To our knowledge this is the second reported case concomitant white papilloma with concomitant HPV in the vocal cords. Bangladesh J Otorhinolaryngol; April 2020; 26(1): 73-76